2018
DOI: 10.1111/ina.12508
|View full text |Cite
|
Sign up to set email alerts
|

PVC flooring at home and uptake of phthalates in pregnant women

Abstract: Phthalates are used as plasticizers in polyvinyl chloride (PVC) materials and it is known that phthalates may migrate into the surrounding environment and then become a source for human uptake. The aim of the study was to investigate whether residential PVC flooring was related to the urinary levels of phthalate metabolites determined in pregnant women. The data were from the Swedish SELMA study where sampling was conducted during the time period 2007‐2010. Spot urine samples from 1674 women at the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…[37] A Swedish study of 1,674 pregnant women showed that polyvinyl chloride ooring in the kitchen and the parents' bedrooms was associated with higher levels of urinary MBzP in the rst trimester. [38] In the present study, a positive correlation was only found between urinary MBzP concentrations and the development of AD in a meta-analysis. During the process of merging data for meta-analysis, the categorical scale of prenatal urinary phthalate exposure levels was converted to a continuous scale following Soomro et al [26] and Wang et al [30] The transformed OR might affect the overall results.…”
Section: Discussioncontrasting
confidence: 59%
“…[37] A Swedish study of 1,674 pregnant women showed that polyvinyl chloride ooring in the kitchen and the parents' bedrooms was associated with higher levels of urinary MBzP in the rst trimester. [38] In the present study, a positive correlation was only found between urinary MBzP concentrations and the development of AD in a meta-analysis. During the process of merging data for meta-analysis, the categorical scale of prenatal urinary phthalate exposure levels was converted to a continuous scale following Soomro et al [26] and Wang et al [30] The transformed OR might affect the overall results.…”
Section: Discussioncontrasting
confidence: 59%
“…PAEs are molecules that are not covalently linked to the matrix and show a tendency to migrate, especially in the presence of lipophilic compounds and/or in the event of mechanical or thermal stress [11]. For example, a generic product containing PVC (it may include more than 40% of DEHP) or other products containing such molecules produces a typical release of PAEs into the environment [12,13]. Therefore, PAEs represent ubiquitous contaminants and decompose with both exposure to sunlight and aerobic microbial activity; they tend to adsorb soil particles, sediments, and humus where they are protected from sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…WQS was specifically developed to assess the joint effect of a combination of chemicals measured as a mixture. Applications have included metals and organics [26, 27]. Consider a set of M correlated metal concentrations at a single time point that are grouped into quantiles, q m , and an outcome of interest y .…”
Section: Methodsmentioning
confidence: 99%